Rituximab in children with myelin oligodendrocyte glycoprotein antibody and relapsing neuroinflammatory disease. (30th August 2019) - Albassam, Fahad; Longoni, Giulia; Yea, Carmen; Wilbur, Colin; Grover, Stephanie A; Yeh, E Ann
Abstract : The aim of this study was to evaluate tolerability of and response to rituximab in children with myelin oligodendrocyte glycoprotein (MOG) antibody‐positive relapsing neuroinflammatory disease. This was an observational study of prospectively collected data on 12 consecutive children (eight females, four males; median age at onset 10y 6mo [interquartile range IQR 7y 2mo–12y 5mo], median follow‐up 2y 1mo [IQR 1y 7mo–2y 6mo]) with central nervous system inflammation and persistent serum MOG immunoglobulin G positivity more than 12 weeks after clinical presentation. Patients received a standardized rituximab treatment protocol. MOG antibody testing was performed following standardized cell‐based methods. Median clinical follow‐up after rituximab induction was 2 years (IQR 1y 7mo–2y 10mo). The relapse rate in the first 12 months posttreatment was 0 (IQR 0–0). After rituximab, two patients relapsed during B‐cell suppression and four showed clinical or radiological disease recurrences at B‐cell reconstitution. Mild‐to‐moderate infusion related adverse events occurred in two patients. Leukopenia developed in seven patients and serum immunoglobulin suppression in five patients with no significant age effect on the risk of their development. None developed severe life‐threatening events. Rituximab‐induced B‐cell suppression was associated with absence of relapses in 10 patients who were MOG‐positive with recurrent disease. Rituximab was well tolerated. The most frequent adverse effects were hypogammaglobulinemia and leukopenia. We recommend monitoring of complete blood counts and immunoglobulins in this population. What this paper adds: Rituximab appears to control disease in most anti‐myelin oligodendrocyte glycoprotein‐positive patients with relapsing neuroinflammatory disease. Rituximab was associated with transitory, mild‐to‐moderate infusion‐related effects. Half of patients treated with rituximab developed leukopenia or hypogammaglobulinemia. No opportunistic infections were observed. What this paper adds: Rituximab appears to control disease in most anti‐myelin oligodendrocyte glycoprotein‐positive patients with relapsing neuroinflammatory disease. Rituximab was associated with transitory, mild‐to‐moderate infusion‐related effects. Half of patients treated with rituximab developed leukopenia or hypogammaglobulinemia. No opportunistic infections were observed. This article is commented on by HACOHEN, MARIGNIER on page 273 of this issue.